Structural equations in educational models: Characteristics and phases in their construction - Víctor Manuel Samperio Pacheco (Universidad de Guadalajara, 2019)
In this article, the characteristics and construction phases of the structural equation models are presented, a useful statistical methodology to study causal relationships through non-experimental information, specifically when the relations are of the linear type. We adopt the strategy of model development through the use of systems of structural equations, in which a model is proposed and the purpose is to improve it through the modification of its structure or its measurements. The maximum likelihood method was used to obtain the common factors. The proposal was made based on the Technological Pedagogical Content Knowledge (TPACK) model. The results obtained from the factorial analysis where user satisfaction was analyzed when they use a Learning Management System to support their face-to-face classes at the Autonomous University of the State of Hidalgo, indicate that there is a strong correlation between the parameters of the TPACK model and the satisfaction of the students, not with the socio-cultural factors. Nor is there a correlation between sociocultural factors and student satisfaction. The importance of this research is the contribution of a model that allows us to determine the satisfaction of students through the model of structural equations with the TPACK model.